2017
DOI: 10.1186/s40529-016-0157-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, physiological, cytological and phytochemical studies in diploid and colchicine-induced tetraploid plants of Fagopyrum tataricum (L.) Gaertn

Abstract: BackgroundTartary buckwheat are very popular as an important functional food material and its cultivation is very widespread in our whole world, but there obviously lack works in the researches of genetic breeding for agricultural and medicinal utilization. The aim of this study is to obtain good germplasm resources for agricultural and medicinal use of tartary buckwheat (Fagopyrum tataricum) by inducing the tetraploid plants.ResultsFour cultivars of F. tataricum, that is, Qianwei 2#, Jinku 2#, Chuanqiao 1#, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…1A). Increasing concentrations and exposure times of colchicine have been shown to inhibit growth and shoot regeneration of explants (Javadian et al, 2017; Wang et al, 2017a). Moreover, higher concentrations of colchicine with longer exposure times can be toxic to plants leading to tissue abnormalities (Megbo, 2010) and dead (Mondin et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1A). Increasing concentrations and exposure times of colchicine have been shown to inhibit growth and shoot regeneration of explants (Javadian et al, 2017; Wang et al, 2017a). Moreover, higher concentrations of colchicine with longer exposure times can be toxic to plants leading to tissue abnormalities (Megbo, 2010) and dead (Mondin et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that colchicine treatment induced phenotypic changes in the regenerated brahmi. Several published studies have reported that colchicine-induced wide morphological variations such as leaf arrangement and size in Platycodon grandiflorus (Wu et al, 2011) and Hebe (Gallone et al, 2014), stomatal size in Pogostemon cablin (Yan et al, 2016) and cassava (Mondin et al, 2018), and leaf, flower, and seed size in Fagopyrum tataricum (Wang et al, 2017a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations